Muslim Women and Pious Learning in Denmark - Schmidt Lyngsøe, Maria Lindebæk (Middle East and Islamic Studies E-Books Online, Collection 2026, 2026)
Based on ethnographic fieldwork, this book investigates how and why Danish Muslim women engage as teachers and students in Islamic educational activities. It does so by focusing on the learning trajectories, knowledge disseminating activities, and class interactions of the women, showing that they involve themselves in a variety of activities to stay continuously engaged, and that this is a way of becoming pious. The book makes evident that this becoming is dependent on the embeddedness of the individual in a web of relations to both this- and otherworldly others. As such, the book promotes a relational understanding of piety formation and religious engagement that are informative to studies of religious life beyond Islam.